2021
DOI: 10.53342/pharmasci.v6i2.198
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Antiretroviral Combinations to CD4 Levels of HIV TB Patiens in RSUD H.Abdul Manap Jambi

Abstract: The cases of Human Immunodeficiency Virus (HIV) infection are increasing every year. This case is a disease that is very rapidly transmitted throughout the world. HIV increases the risk of developing tuberculosis (TB) and conversely TB infection increases HIV progression. In 2017, it is estimated that 10 million people have HIV TB. Combination of antiretrovirals is the basis for the management of antiretroviral therapy for HIV / AIDS patients, because it can reduce resistance, suppress HIV replication effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…Our results showed that during 2 years ART CD4 counts increased with time (p=0.000), which is similar to other studies (5,22) Our study found that the maximum value at (24). INR has been associated with a number of factors, such as older age, a long duration of the HIV infection prior to HAART, coinfection with hepatitis C, and a low CD4 count nadir.…”
Section: The Effect Of Antiretroviral Therapy Duration (Arv) On Cd4 C...supporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed that during 2 years ART CD4 counts increased with time (p=0.000), which is similar to other studies (5,22) Our study found that the maximum value at (24). INR has been associated with a number of factors, such as older age, a long duration of the HIV infection prior to HAART, coinfection with hepatitis C, and a low CD4 count nadir.…”
Section: The Effect Of Antiretroviral Therapy Duration (Arv) On Cd4 C...supporting
confidence: 91%
“…INR has been associated with a number of factors, such as older age, a long duration of the HIV infection prior to HAART, coinfection with hepatitis C, and a low CD4 count nadir. The CD4 count nadir appears to be most critical for the recovery of CD4+ cells (24,25).…”
Section: The Effect Of Antiretroviral Therapy Duration (Arv) On Cd4 C...mentioning
confidence: 99%
“…(13) In Indonesia, sexual activity carries the largest risk of HIV/AIDS transmission (62.5%), followed by drug injection (16.1%), pregnancy (2.7%), and homosexuality (2.4%). (14) In Indonesia, the prevalence of HIV in TB patients is around 2.4%. TB is the most common opportunistic infection (49%) in people with HIV/AIDS.…”
Section: Health Dynamicsmentioning
confidence: 99%